If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1t + 15 = 2 Reorder the terms: 15 + -1t = 2 Solving 15 + -1t = 2 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -1t = 2 + -15 Combine like terms: 15 + -15 = 0 0 + -1t = 2 + -15 -1t = 2 + -15 Combine like terms: 2 + -15 = -13 -1t = -13 Divide each side by '-1'. t = 13 Simplifying t = 13
| 3u+147=180 | | x(x+1)=1024 | | x=15+7x-81 | | -7+3+-5= | | 6x-19=10x-79 | | 10m=(3m-11)-17 | | -2x^3+19X^2-38x+21=0 | | z=2z-68 | | 3x-11=2(x-3)-8 | | -26+17= | | 1=-3xy | | 4t+5=2 | | 3(1-2x)=6-6x | | 16+-12+-7= | | x^2+X(c-b)+(c-a)(a-b)=0 | | 4x-90=3x-60 | | 5x+3y=56 | | abc-cba=973 | | -9x+1=-26 | | abc-cba=891 | | 4*sinx*cosx+2*cosx+1=0 | | abc-cba=675 | | 3a+7+2a=18-9 | | abc-cba=456 | | 15z-75=180 | | x-11=4x+44 | | 6(x-3)=2(3x-5) | | 4t-66=5t-87 | | sin(2x)+2*cosx+1=0 | | X^4-x^3-27x^2+25x+50=0 | | 4(5x-3)=2x-34 | | 8q-67=6q-35 |